Effective degradation of cefuroxime by heterogeneous photo-Fenton under simulated solar radiation using α-Fe2O3-TiO2. Issue 6 (December 2021) - Hernández-Coronado, Edgar E.; Ruiz-Ruiz, Edgar J.; Hinojosa-Reyes, Laura; Beltrán, Fernando J.; López-Gallego, Jorge; Gracia-Pinilla, Miguel Á.; Villanueva-Rodríguez, Minerva
Abstract: In this work, the photocatalytic degradation of the antibiotic cefuroxime (CFX) was evaluated by heterogeneous photo-Fenton using α-Fe2 O3 -TiO2 as a catalyst under simulated solar radiation and varying the concentration of H2 O2 added. The materials α-Fe2 O3 -TiO2 modified with different amounts of α-Fe2 O3 were prepared by the sol-gel method. The materials were characterized by X-ray diffraction, atomic absorption spectroscopy, scanning electron microscopy, transmission electron microscopy, UV–Vis diffuse reflectance spectroscopy, N2 adsorption-desorption, and X-ray photoelectronic spectrometry. The Fe2 O3 incorporation into TiO2 increased surface area, decreased Eg value, and improved the degradation efficiency of CFX. The photocatalytic tests were conducted under simulated sunlight. The best results were obtained at pH 3, (1.0% wt.) α-Fe2 O3 -TiO2, and 5.3 mmol L −1 H2 O2, achieving complete degradation of CFX and 73% mineralization at 150 kJ m −2 of accumulated radiation. A synergistic effect between heterogeneous photocatalysis and photo-Fenton process was observed using α-Fe2 O3 -TiO2 as the catalyst. Inorganic ions such as nitrate and sulfate, short-chain carboxylic acids (organic ions) were detected during degradation. Also, the stability of α-Fe2 O3 -TiO2 was demonstrated during five consecutive cycles in the CFX degradation with minimum iron leaching, which makes it a suitable catalyst for organic contaminants elimination by heterogeneous photo-Fenton. Graphical Abstract: ga1 Highlights: Cefuroxime was 100% degraded and 73% mineralized by TiO2 -Fe2 O3 /H2 O2 under simulated sunlight. The optimal amount of Fe2 O3 in TiO2, H2 O2 and pH was established for cefuroxime elimination. A synergistic effect was observed between heterogeneous photocatalysis and the Fenton reaction. Fe2 O3 -TiO2 demonstrated high stability during five cycles of treatment with minimum Fe leachate.